2022
DOI: 10.18332/tid/146363
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette prevalence among Malaysian adults and types and flavors of e-cigarette products used by cigarette smokers who vape: Findings from the 2020 ITC Malaysia Survey

Abstract: INTRODUCTION E-cigarettes (ECs) have become increasingly common in many countries, including Malaysia. The prevalence of EC use increased in Malaysia from 0.8% in 2011 to 4.9% in 2019. Three quarters of Malaysian EC users also smoke combustible cigarettes, and the prevalence of EC use among Malaysian smokers in 2014 was consistent with the prevalence of use among smokers from Canada and the US in 2016. The purpose of this study was to estimate the prevalence of EC use among Malaysian adults aged ≥18 years in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Studies conducted in 2011-2019 have found that 8-14% of Malaysian cigarette smokers use ECs at least monthly 7,10,11 . A more recent study conducted in 2020 found that 17% of daily cigarette smokers in Malaysia also used ECs daily 12 , a striking finding since only 12.8% of cigarette smokers in England used ECs daily in 2020 13 . In summary, these studies suggest that EC use in Malaysia is very high.…”
Section: Introductionmentioning
confidence: 98%
“…Studies conducted in 2011-2019 have found that 8-14% of Malaysian cigarette smokers use ECs at least monthly 7,10,11 . A more recent study conducted in 2020 found that 17% of daily cigarette smokers in Malaysia also used ECs daily 12 , a striking finding since only 12.8% of cigarette smokers in England used ECs daily in 2020 13 . In summary, these studies suggest that EC use in Malaysia is very high.…”
Section: Introductionmentioning
confidence: 98%
“…This is likely due in large measure to the lower prevalence of HTPs (12.0%) compared with ECs (33.8%) among Malaysian smokers, which has also been detected in another ITC MYS1 study. 29 It will be important to track changes in EC and HTP use and their use in attempts to quit in Malaysia over time.…”
Section: Discussionmentioning
confidence: 99%
“…Malaysia has a big e-cigarette market with a prevalence of daily use at 5.8% in 2020 among adults and past 30-day e-cigarette use at 9.1% among youth aged 13–19 years [ 23 ]. E-cigarette marketing and sales are not regulated in Malaysia.…”
Section: Introductionmentioning
confidence: 99%